Effectiveness of intensive nutrition intervention on nutritional, side-effects and functional outcomes among head and neck cancer outpatients on radiotheraphy - Jamhuri, Norshariza (2020)
Malnutrition is common in head and neck cancer (HNC) patients even prior to treatment. An intensive nutrition intervention (INI) might able to improve their nutritional status. However, malnutrition risk is greater among HNC outpatients due to the limited contact time with dietitian, absence of close monitoring and oral nutrition supplement (ONS) provision compared to HNC inpatients plus that there was limited research on the effectiveness of INI among HNC outpatients. Thus, this leads to significant gap in optimising the deliverance of dietitians’ services in this area. An open labelled pragmatic randomised controlled trial study was conducted to ascertain the effectiveness of INI (prescription and provision of ONS, dietary consultation and frequent follow-up) vs routine care (RC) which includes dietary consultation, frequent follow up and ONS prescription only, among HNC outpatients towards nutritional, side effects and functional outcome. A total of 36 subjects were recruited from the HNC outpatients list in radiotherapy clinic at National Cancer Institute, Putrajaya, obtained from the online system and randomised into the INI and RC group using online randomiser software. Patients who already started on ONS, tube feeding and cancer treatments prior to the study period were excluded. Patient Generated Subjective Global Assessment (PG-SGA) and Head and Neck Symptoms Checklist (HSNC) were used to assess nutritional and side effect status whilst handgrip strength (HGS) was used to assess the functional status of study subjects. Parametric test was used for normally distributed data unless otherwise stated and univariate analysis was used for repetitive measurements. A modified intention to treat principle (ITT) and per protocol (PP) principle were used for fair comparisons among treatment groups which reflects clinical effectiveness in actual practices and built confidence in study results when both analyses came into same conclusions. Changes in nutrition outcomes including weight, body mass index (BMI), fat mass (FM) and muscle mass (MM); side-effects outcome (nutrition impact symptoms (NIS) and HGS were observed and analysed. Overall median weight was 70.6±16.8kg with 52.8% overweight. Most subjects were well-nourished, yet the NIS score was 21+5 before treatment started. Significant weight loss (p<0.001), reduction in BMI (p<0.001), lower FM (p<0.001), reduction in MM (p<0.001), and higher NIS score (p<0.001) within subjects in both groups were observed. The provision of INI produced positive changes in handgrip strength (HGS). Improvements in HGS were reported in INI subjects. Inadequate overall intake in energy (< 25kcal/kg body weight) and protein in both groups (< 0.8gram protein/ kg body weight) compared to the recommended requirement of 30kcal/kg body weight and 1.2-gram protein/kg body weight were observed. FM reduction was significantly different (p=0.013) between groups. The INI group had a lower percentage of weight loss, FM loss, BMI loss and MM loss compared to the RC group. Combination of ONS prescription and provision, dietary consultation and frequent follow-up could prevent further deterioration in nutritional, side effects and functional outcomes among HNC outpatients and can be adapted in outpatient setting as standard procedures in HNC dietary care against malnutrition.